Simultaneous Synthesis and Consolidation of Nanostructured MgSiO3-Mg3Al2Si3O12 Composite and Its Mechanical Properties - Kang, Hyun-Su; Shon, In-Jin; Doh, Jung-Mann; Yoon, Jin-Kook (JAPAN INST METALS & MATERIALS, 2014)
Nanopowders of MgO, Al2O3 and SiO2 were made by high energy ball milling. The simultaneous synthesis and consolidation of nanostuctured MgSiO3-Mg3Al2Si3O12 composites from milled 4MgO, Al2O3 and 4SiO(2) powders was investigated by the high-frequency induction heated sintering process. The advantage of this process is that it allows very quick densification to near theoretical density and inhibition of grain growth. Highly dense nanostructured MgSiO3-Mg3Al2Si3O12 composites were produced with a simultaneous application of 80 MPa pressure and an induced current within 1 mm. The microstructure, sintering behavior and mechanical properties of MgSiO3-Mg3Al2Si3O12 composite were evaluated.
Keywords: ACTIVATED SYNTHESIS; GROWTH; TI